Aktivitas Perikanan Tangkap di Kawasan Konservasi TWP Gili Sulat dan Gili Lawang, Kabupaten Lombok Timur, Provinsi NTB - Ayu Adhita Damayanti; Soraya Gigentika; Destikawati; Lalu Ferdi Alfarisi Murdin; Muh. Marwan; Rahfika; Rahman Jayawangsa (Jurnal Ilmu Kelautan Lesser Sunda, 2022)
The TWP Gili Sulat and Gili Lawang are one of the marine conservation areas in NTB Province. In this area, there is a sustainable fisheries zone that is used by fishermen around the area. However, the lack of information regarding capture fisheries activities in the Gili Sulat and Gili Lawang TWP areas has caused the NTB Provincial Government to have not been able to make decisions for regulating capture fisheries activities in these areas. Based on these conditions, preliminary research on capture fisheries activities carried out by fishermen in the Gili Sulat and Gili Lawang TWP areas are important. Data collection in this study was carried out in Sugian Village and Labuhan Pandan Village using the purposive sampling method. The data analysis used in this research is descriptive analysis. This study indicates that capture fisheries activities in the Gili Sulat and Gili Lawang TWP areas are carried out by artisanal fishermen, where fishing activities fall into the category of small-scale fisheries. The fishing gear used by fishermen in the Gili Sulat and Gili Lawang TWP areas are hand rods, gill nets, anco, and arrows. The fishing vessels that are dominantly operated by fishermen in the area are 5-7 meters and 8-10 meters. The fishing area for fishermen in the Gili Sulat and Gili Lawang TWP areas is 10 meters to 10 km from the fishing base, but some fishermen carry out fishing activities within 1.5 – 2.5 miles from the fishing base. The most common type of fish caught by fishermen in the Gili Sulat and Gili Lawang TWP areas is anchovy.